Identifying the “source” of recognition memory deficits in patients with Huntington's disease or Alzheimer's disease: Evidence from the CVLT-II - Fine, Eric M. (2008)
The present study compared the performance of individuals with Huntington's disease (HD) and Alzheimer's disease (AD) on three types of California Verbal Learning Test–Second Edition (CVLT-II) recognition discriminability indices (RDI): Source, Novel, and Total. The HD and AD groups did not differ significantly on Source RDI (all 16 targets versus the 16 previously presented, List B, distractors). However, HD patients performed significantly better than AD patients on Total RDI (all 16 targets versus all 32 distractors) and Novel RDI (all 16 targets versus 16 new distractors). Implications of these findings on the differentiation of the memory disorders associated with HD and AD are discussed.